Determinasi Gaya Kepemimpinan, Motivasi, dan Budaya Organisasi Terhadap Kinerja Pegawai: Peran Mediasi Kepuasan Kerja di BP2P Nusa Tenggara II - Aryanto Andrianus Kollawila; Stanis Man (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
This article examines the determinants of employee performance and analyzes the correlation between these determinants and satisfaction and performance. This article discusses leadership style, motivation, organizational culture and job satisfaction as the main aspects. The purpose of this scientific article is to identify interrelated hypotheses among the above factors for use in future writings. This scientific method uses qualitative techniques and literature reviews. This article is based on various related journals to formulate new hypotheses regarding leadership style that results in job satisfaction, organizational culture results in job satisfaction, motivation results in job satisfaction, leadership style results in employee performance, organizational culture results in employee performance, the role of motivation in employee performance, and the relationship between job satisfaction and employee performance.